(untitled) (The Research of Medical Science Review, 2025)
Background: It is known that adherence to pharmacological treatment in schizophrenia patients can be increased by working on their insight into their disorder. Therefore, the current study was designed to see the patterns of positive, negative and general psychopathological symptoms among patients with schizophrenia. Methodology: A total of 440 patients were taken from the different psychiatric hospitals in Karachi, Pakistan. All the patients were diagnosed with schizophrenia disorder and are under treatment. Patients with comorbid conditions were excluded from the study. Patients’ age range was 25-45 years with M=29.33, SD=7.35 years. All the participants were taken from middle-income groups through purposive sampling. Results: At initial screening prevalence of positive symptoms was estimated in a high range which is > 55-73%, the prevalence of negative symptoms was 54-72% and the general psychopathological symptoms were estimated at 25-80% in the sample, which reflects that there is a high range of schizophrenia symptoms Conclusion: It is concluded that there is a high risk of prevalence of positive, negative and general psychopathological symptoms among patients with schizophrenia and these symptoms' severity might be increased if these symptoms are not managed using proper treatment modalities.